The Level of Convergence to Shari’ah Principles and Corporate Profitability - Deniz Parlak; Mehmet Emin Yildiz; Naci Yılmaz (Journal of Islamic Monetary Economics and Finance, 2024)
This study constructs a Shari'ah convergence index for 1,362 companies operating in 10 different Islamic countries between 2017 and 2021 and assesses its relation to corporate profitability. Shari’ah screening variables are based on existing Shari’ah screening literature and applications, and variable weights are assigned using the Integrated Determination of Objective Criteria Weights (IDOCRIW) technique, a widely used, multi-criteria decision-making method. The results suggest that 4% of the sample is completely non-compliant as they engage in non-permissible business activities, 82% has a non-compliant activity level below 30% and the remaining 14% has a non-compliant activity level between 41 and 99%. Our panel data regression analysis shows that, while the Shari'ah convergence index does not affect operating profitability, it does have a statistically positive effect on total corporate profitability. These findings are attributable to two factors, interest burden and debt level. It seems that, for Islamic companies, The high cost of debt service may offset the advantage of high leverage on profitability. Acknowledgment We thank to Prof. Abdullah Yalaman for his valuable comments and to Eric Laden for his proofreading.